2021
DOI: 10.1039/d1nr06285a
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of metal oxide catalysts for electrocatalytic water splitting

Abstract: The review introduces the mechanisms of heterogeneous hydrogen evolution (HER) and oxygen evolution reactions (OER), summarizes in-situ characterization techniques and surveys strategies to boost the activities of metal oxide electrocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 176 publications
0
35
0
Order By: Relevance
“…Generally, the TOF of heterogeneous electrocatalysts is calculated by considering the active sites present on the electrocatalyst surface. The TOF can be calculated using the following equation [ 114 ] TOF = j N A n F Γ where j , N A , n , F , and Γ are the current density at an overpotential, Avogadro's constant, number of electrons transferred, Faraday constant, and number of moles of active sites present in the electrocatalyst, respectively. The concentration of the active sites can be determined using different techniques such as cyclic voltammetry (CV) and inductively coupled plasma spectrometry by assuming that all the metal centers present in the electrocatalyst are electrocatalytically active.…”
Section: Parameters Used To Evaluate Electrocatalytic Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Generally, the TOF of heterogeneous electrocatalysts is calculated by considering the active sites present on the electrocatalyst surface. The TOF can be calculated using the following equation [ 114 ] TOF = j N A n F Γ where j , N A , n , F , and Γ are the current density at an overpotential, Avogadro's constant, number of electrons transferred, Faraday constant, and number of moles of active sites present in the electrocatalyst, respectively. The concentration of the active sites can be determined using different techniques such as cyclic voltammetry (CV) and inductively coupled plasma spectrometry by assuming that all the metal centers present in the electrocatalyst are electrocatalytically active.…”
Section: Parameters Used To Evaluate Electrocatalytic Activitymentioning
confidence: 99%
“…[ 119 ] In situ XAS in combination with the Extended X‐Ray absorption fine structure (EXAFS) and X‐Ray absorption near edge structure (XANES) can be utilized to detect the modifications of the electronic structure as well as the local geometric environments of the atoms of the electrocatalysts. [ 114 ] Bell and coworkers observed the octahedral occupancy of Fe 3+ ions in Ni 1–x Fe x OOH and very short Fe–O bond distances by operando XAS technique during alkaline OER. [ 120 ] The authors also indicated that the amount of Fe (<25%) was critical in achieving Fe‐doped γ‐Ni 1−x Fe x OOH to exhibit high OER activity.…”
Section: Parameters Used To Evaluate Electrocatalytic Activitymentioning
confidence: 99%
See 3 more Smart Citations